32nd European Solid-State Device Research Conference 2002
DOI: 10.1109/essderc.2002.194954
|View full text |Cite
|
Sign up to set email alerts
|

Process Integration of Crystalline Pr2O3 High-k Gate Dielectrics

Abstract: In this work we report on the process integration of crystalline praseodymium oxide (Pr 2 O 3 ) high-k gate dielectric. Key process steps which are compatible with the high-k material have been developed and were applied for realisation of MOS sructures. For the first time Pr 2 O 3 has been integrated successfully in a conventional MOS process with n+ poly-silicon gate electrode. The electrical properties of Pr 2 O 3 MOS capacitors are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Alternative high-k gate dielectrics like HfO 2 (11) are currently investigated as replacement for thermally grown silicon dioxide (SiO 2 ) in an attempt to overcome the severe gate tunneling currents. Recently it was shown that rare earth high-k dielectrics epitaxially grown on the Sisurface by molecular-beam-epitaxy (MBE) have excellent dielectric properties (12). Crystalline praseodymium oxide (Pr 2 O 3 ) films (13 -15) and gadolinium oxide (Gd 2 O 3 ) films (16,17) have been successfully integrated in CMOS technologies.…”
Section: Electrical Characterization Of High-k Gate Dielectricsmentioning
confidence: 99%
“…Alternative high-k gate dielectrics like HfO 2 (11) are currently investigated as replacement for thermally grown silicon dioxide (SiO 2 ) in an attempt to overcome the severe gate tunneling currents. Recently it was shown that rare earth high-k dielectrics epitaxially grown on the Sisurface by molecular-beam-epitaxy (MBE) have excellent dielectric properties (12). Crystalline praseodymium oxide (Pr 2 O 3 ) films (13 -15) and gadolinium oxide (Gd 2 O 3 ) films (16,17) have been successfully integrated in CMOS technologies.…”
Section: Electrical Characterization Of High-k Gate Dielectricsmentioning
confidence: 99%
“…Alternative high-k gate dielectrics like HfO 2 (12) are currently investigated as replacement for thermally grown silicon dioxide (SiO 2 ) in an attempt to overcome gate tunneling currents. Recently it was shown that rare earth high-k dielectrics epitaxially grown on Si-surface by molecular-beam-epitaxy (MBE) have excellent dielectric properties (13). Crystalline praseodymium oxide (Pr 2 O 3 ) films (14 -16) and gadolinium oxide (Gd 2 O 3 ) films (17,18) have been successfully integrated in CMOS technologies.…”
Section: Characterization Of High-k Gate Dielectricsmentioning
confidence: 99%
“…They main difference between both structures is expected to originate from the different gate dielectric, which may affect the silicon-insulator interface and the channel region close to this interface. Previously, Pr 2 O 3 high-k NMOSFETs have been fabricated using a conventional poly-silicon gate process technology [3] with a k-value of approx. 30, corresponding to an EOT of about 20 Å-25 Å.…”
Section: Device Fabrication and Structurementioning
confidence: 99%
“…Praseodymium oxide (Pr 2 O 3 ) was the first epitaxially grown rare-earth material to be investigated as gate dielectric [1,2]. Fully functional MOSFETs have been fabricated for the first time by our group [3,4] using conventional poly-silicon gate electrodes. Electrical properties and discussion of device properties can be found in [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%